The Effect of GeoGebra Augmented Reality Learning Media on Students’ Learning Outcomes in Solid Geometry in Class IV at SDN Sikumana 2 Kota Kupang - Angeline Arnoldus; Yulsy M. Nitte; Marice Jublina Penu; Skolastika Diana Novita Nanga; Yohana Yuvita Siba (JURNAL PENDIDIKAN IPS, 2025)
This study aims to determine the effect of using Augmented Reality (AR)-based learning media through the GeoGebra application on the mathematics learning outcomes of fourth-grade students in the topic of geometric solids. This research was motivated by the low understanding of students regarding geometric solid concepts, which are abstract and difficult to visualize through conventional media. The method used is a quasi-experimental design with a nonequivalent control group. The sample consisted of two classes, each with 15 students, divided into an experimental group and a control group. The research instruments included learning outcome tests and student response questionnaires. The results showed that students who learned using GeoGebra AR showed a significant improvement in learning outcomes compared to those taught by conventional methods. GeoGebra AR media provided a more concrete, interactive, and engaging learning experience. Thus, AR-based learning media can be an effective alternative to enhance students' conceptual understanding of mathematics in elementary schools.